Keeping up with the Joneses – the Effect of Individual Cultural Values on Conspicuous Consumption - Aslıhan Kiymalioğlu; Eyyüp Yaraş; Duygu Aydin Ünal (Istanbul Business Research (IBR), 2018)
This paper aims to investigate the relationship between individual cultural values and brand consciousness, and the effect of this relationship on conspicuous consumption. Individual cultural values scale developed by Yoo et al. (2011), based on five dimensions of national culture propounded by Hofstede, were used to develop hypotheses pertaining to their effects on brand consciousness and the effect of brand consciousness on conspicuous consumption. Results of the study provide support for some of the hypothesised effects which suggest that indeed, certain dimensions of culture are key factors in determining whether or not consumers use brands as status symbols and for showing off. The finding that conspicuous consumption is used as a tool for expressing our power distance and masculinity values reveals the symbolic value of consumption. These results offer possibilities for using cultural values on an individual level and analysing their effect on consumption attitudes of consumers.
Keywords: M0; 650; Conspicuous consumption; Individual national cultures; Brand consciousness